EFFECTS OF HEALTH EDUCATION LEARNING MANAGEMENT USING CREATIVE THINKING CONCEPT AND BRAINSTROMING TECHNIQUE ON LEARNING ACHIVEMENT AND CREATIVE THINKING FOR PRIMARY SCHOOL STUDENTS - Chuleekran, Anuchit; Sarayuthpitak, Jintana; Bunluesak , Jintana (Academic Journal of Thailand National Sports University, 2022)
Purposes: To study the effects of health education learning management using creative thinking concept and brainstorming technique on learning achievement and creative thinking for primary school students. Methods: The subjects were 60 sixth grade students, using simple random sampling into 30 students for the experimental group who were assigned to study under the health education learning management with the creative thinking concept and brainstorming technique learning while 30 students of the control group were assigned to study with the conventional teaching method. The research instruments were comprised of 8 health education lesson plans using the creative thinking concept and brainstorming technique learning with IOC 0.96 and the data collection instruments included the learning achievement in the area of knowledge, attitude, practice tests and creative thinking test with IOC 0.92, 0.84, 0.96 and 1.00, reliabilities were 0.89, 0.80, 0.83 and 0.80, The data were analyzed by mean, standard deviation and t-test. Results: The research findings were as follows: The mean scores of the learning achievement in the area of knowledge, attitude, practice and creative thinking of the experimental group students after learning were significantly higher than that before learning at .05 level., and the mean scores of the learning achievement in the area of knowledge, attitude, practice and creative thinking of the experimental group students after learning were significantly higher than that in the control group at .05 level. Conclusion: Health education learning management with the creative thinking concept and brainstorming technique learning effect on learning achievement and creative thinking of sixth grade students were higher than health education learning management with the conventional teaching method.